Inter industry linkages in New Zealand - Iris Claus (New Zealand Government, The Treasury, 2002)
This paper investigates the production structure of the New Zealand business sector using the recently released 1996 input output tables. The analysis is undertaken at the most disaggregated level for which data are available, 126 industries. Indices of backward and forward linkages, measures of industry interconnectedness and a value added production multiplier are calculated. The ranking of industries by degree of connectedness depends on whether direct transactions or both direct and indirect transactions are considered. In 1996, wholesale and retail trade, air transport, services to transport and storage, central government administration, meat processing, and dairy product manufacturing had the strongest backward and forward links with other industries.
Keywords: C67; L16; 330; Input output models; inter industry dependencies